2020
DOI: 10.1186/s12943-020-01231-4
|View full text |Cite
|
Sign up to set email alerts
|

CircRNAs: biogenesis, functions, and role in drug-resistant Tumours

Abstract: Targeted treatment, which can specifically kill tumour cells without affecting normal cells, is a new approach for tumour therapy. However, tumour cells tend to acquire resistance to targeted drugs during treatment. Circular RNAs (circRNAs) are single-stranded RNA molecules with unique structures and important functions. With the development of RNA sequencing technology, circRNAs have been found to be widespread in tumour-resistant cells and to play important regulatory roles. In this review, we present the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 177 publications
(246 reference statements)
0
79
0
Order By: Relevance
“…Since circRNAs regulate target genes of miRNAs by acting as miRNA sponges [ 18 ], the competitive interactions of viral circRNAs and the DE human miRNAs and mRNAs were analyzed in viral infections of Calu-3 cells to investigate the functions of viral circRNAs. In 6 hpi of MERS-CoV, 238 high-confidence viral circRNAs which were defined as those detected by at least two detection tools, with back-splicing junction reads ≥2 and with the length ranging from 200 bp to 2 kbp (Materials and Methods) were identified ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since circRNAs regulate target genes of miRNAs by acting as miRNA sponges [ 18 ], the competitive interactions of viral circRNAs and the DE human miRNAs and mRNAs were analyzed in viral infections of Calu-3 cells to investigate the functions of viral circRNAs. In 6 hpi of MERS-CoV, 238 high-confidence viral circRNAs which were defined as those detected by at least two detection tools, with back-splicing junction reads ≥2 and with the length ranging from 200 bp to 2 kbp (Materials and Methods) were identified ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The circRNAs are reported to have diverse functions in mammals and plants [ 16 , 17 ]. They can function as microRNA (miRNA) sponges, by binding proteins, or by encoding proteins [ 18–20 ]. For example, ciRS-7 contains more than 70 binding sites for miR-7 and correlates with the human disease by affecting miR-7 activity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of circRNAs biogenesis is a remarkably complicated process ( Ma et al, 2020 ). Previous studies indicated that the reverse complementary sequences, like Alu sequences, may facilitate back-splicing by closing up the flanking introns together.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is an effective method to prevent BC recurrence and metastasis following surgical treatment [ 99 ]. However, chemotherapeutic resistance remains a major problem, and a way to track or predict the development of drug resistance would enable better management of BC [ 100 ].…”
Section: Clinical Relevance Of Circrnas In Bcmentioning
confidence: 99%
“…However, chemotherapeutic resistance remains a major problem, and a way to track or predict the development of drug resistance would enable better management of BC [ 100 ]. To this end, some circRNAs were described as associated with drug resistance ( Section 3.2.2 ), and therefore may be relevant as biomarkers in this space [ 99 ]. The mechanism of action in drug resistance has been studied for a number of circRNAs in other types of cancer previously [ 101 , 102 , 103 ], but only a handful of candidates were investigated in detail in BC.…”
Section: Clinical Relevance Of Circrnas In Bcmentioning
confidence: 99%